Strengthening Human Resource Capacity through Human Capital Development Transformation: Evidence from the Protocol and Leadership Communication Unit of Polewali Mandar Regency Government - Ainun Zakinah; Wahdania; Fatmawati; Muchriady Muchran (www.amertainstitute.com, 2026)
This study examines how Human Capital Development (HCD) transformation strengthens human resource capacity within the Protocol and Leadership Communication Unit of the Polewali Mandar Regency Government, Indonesia. In the context of increasing public demands for transparency, responsiveness, and effective communication, local governments are required to develop adaptive and competent human resources. This research aims to analyze the implementation of HCD and to identify supporting and constraining factors influencing its effectiveness in the public sector. A qualitative case study approach was employed, with data collected through in-depth interviews, direct observations, and document analysis involving officials and staff of the unit. The data were analyzed using thematic analysis supported by data triangulation to ensure validity. The findings indicate that HCD initiatives have contributed positively to improving technical and managerial competencies in protocol and leadership communication functions. However, the transformation process faces persistent challenges, particularly limited training budgets, inadequate technological infrastructure, low digital literacy, and bureaucratic constraints. Leadership commitment and organizational support were found to be critical enablers, although their impact remains constrained by structural and resource limitations. This study contributes to the human capital literature by providing empirical evidence from a local government setting, highlighting the gap between HCD policy formulation and operational implementation. Practically, the findings suggest the need for more integrated HCD policies, enhanced investment in digital infrastructure, and continuous capacity-building programs to support sustainable human resource development in the public sector. The study offers insights for policymakers seeking to strengthen institutional performance through strategic human capital transformation.